Introduction - Michael Holquist (Studies in 20th & 21st Century Literature, 1984)
Introduction to the special issue on Mikhail Bakhtin
Keywords: Bakhtin; dialogue; Bakhtian dialogue; superaddress; subject; communication; kerygma